KANDUNGAN KLOROFIL BERBAGAI JENIS DAUN TANAMAN DAN Cu-TURUNAN KLOROFIL SERTA KARAKTERISTIK FISIKO-KIMIANYA - Nurdin Nurdin; Clara Meliyanti Kusharto; Ikeu Tanziha; M. Januwati (Jurnal Gizi dan Pangan, 2009)
The chlorophyll is well known as natural antioxidant which is commonly high  level  in some geen leafy and has potential biological effect for a good  health and  has been proved has antioxidant and antimutagenic activity. In fact, a high content of chlorophyll is available in nature but in contrast its found commercially in Indonesia as imported product with a high price. The objectives of this study were to determine of chlorophyll level  of various leaves (Premna oblongifolia Merr., Saurpus androgynus  Merr. Centella asiatica, and Morus alba L),  to produce copper-chlorophyll derivative powder, and to observe its physico-chemical properties. The research showed that cincau leaf had higher level of chlorophyll than other leaves, meanwhile cincau leaf used as material of copper-chlorophyll derivative. Cincau leaves chlorophyll extract solution with Cu2+  100 mg/l level produce the cincau copper-chlorophyll derivative powder with highest  pH, solubility, and geenness compare to other copper levels. The cincau copper-derivate chlorophyll  powder contained chlorophyll 3986 mg/kg, b-carotene 33.8 mg/kg, and contained alkaloid, saponin, tanin, steroid, and glycoside.